Transcriptional profiling of Vibrio parahaemolyticus exsA reveals a complex activation network for type III secretion - Liu, Aaron C.; Thomas, Nikhil A. (Frontiers in Microbiology, 2015)
Vibrio parahaemolyticus (Vp) is a marine halophilic bacterium that is commonly associated with oysters and shrimp. Human consumption of contaminated shellfish can result in Vp mediated gastroenteritis and severe diarrheal disease. Vp encodes two type 3 secretion systems (T3SS-I and T3SS-II) that have been functionally implicated in cytotoxicity and enterotoxicity respectively. In this study, we profiled protein secretion and temporal promoter activities associated with exsA and exsB gene expression. exsA is an AraC-like transcriptional activator that is critical for activating multiple operons that encode T3SS-1 genes, whereas exsB is thought to encode an outer membrane pilotin component for T3SS-1. The exsBA genetic locus has two predicted promoter elements. The predicted exsB and exsA promoters were individually cloned upstream of luxCDABE genes in reporter plasmid constructs allowing for in situ, real-time quantitative light emission measurements under many growth conditions. Low calcium growth conditions supported maximal exsB and exsA promoter activation. exsB promoter activity exhibited high basal activity and resulted in an exsBA co-transcript. Furthermore, a separate proximal exsA promoter showed initial low basal activity yet eventually exceeded that of exsB and reached maximal levels after 2.5 hours corresponding to an entry into early log phase. exsA promoter activity was significantly higher at 30oC than 37oC, which also coincided with increased secretion levels of specific T3SS-1 effector proteins. Lastly, bioinformatic analyses identified a putative expanded ExsA binding motif for multiple transcriptional operons. These findings suggest a two wave model of Vp T3SS-I induction that integrates two distinct promoter elements and environmental signals into a complex ExsA activation framework.